Marco legislativo del Estado de Michoacán para el desarrollo local: revisión y propuesta - Herrera Torres, Hugo Amador (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
In the course of last two decades the economies and societies of the developed and underdeveloped country have suffered processes of structural change. It is a phase of restructuring technological and organizational that it affects to the forms of production, to the managerial management and to the proper nature of the State. In the base of this phase of technological, economic and organizational restructuring that constitutes a process of social, institutional and cultural change there must get innovations that they generate funcionamientos competitive in the different sectors and economic activities. In this stage, the signatures and the most dynamic regions offer strategic answers to the challenges that the increase of the competition presents on the markets. In the reforms of modernization of the State and in the changes in the strategies of productive restructuring they emphasize the local initiatives, these strengthen the immaterial factors of the development and the organization of the territory. The local development is a process of growth and structural change of the economy of a region, in which there can be identified economic, social, cultural, political, administrative and institutional dimensions.

En el transcurso de las dos últimas décadas las economías y sociedades de los países desarrollados y subdesarrollados han sufrido procesos de cambio estructural. Es una fase de reestructuración tecnológica y organizativa que afecta a las formas de producción, a la gestión empresarial y a la propia naturaleza del Estado. En la base de esta fase de reestructuración tecnológica, económica y organizativa que constituye un proceso de cambio social, institucional y cultural se deben introducir innovaciones que generen funcionamientos competitivos en los diferentes sectores y actividades económicas. En este escenario, las firmas y las regiones más dinámicas ofrecen respuestas estratégicas a los retos que presenta el aumento de la competencia en los mercados. En las reformas de modernización del Estado y en los cambios en las estrategias de reestructuración productiva destacan las iniciativas locales, éstas fortalecen los factores inmateriales del desarrollo y la organización del territorio. El desarrollo local es un proceso de crecimiento y cambio estructural de la economía de una región, en el que se pueden identificar dimensiones económicas, sociales, culturales, políticas, administrativas e institucionales.
Facultad de Economía Vasco de Quiroga. Maestría en Ciencias en Gestión Estratégica del Desarrollo
Keywords: info:eu-repo/classification/cti/5; FEVAQ-M-2006-0001; Reestructuración organizativa; Michoacán; Desarrollo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4940